A função do STJ e do STF e os requisitos de admissibilidade dos recursos especial e extraordinário com as inovações do novo Código de Processo Civil - Bonagura, Anna Paola de Souza (2016)
This work aims to study the function of the Superior Court of Justice and Supreme Federal Court and there way of ruling both special and extraordinary appeal to cause the reasoning uniformity of the law. Review of the origins of such Courts. Evolving of legislation regarding such Courts, appeals and correspondent jurisprudence. Focus on STJ and STF regarding the admissibility of such appeals. Considering of relevance reasoning procedure and current “repercussão geral” system. Based on such this work aims to analyze how such Court are developing the so called “jurisprudência defensiva” as filter. In such scenario this work address the innovation promoted by new civil procedural code that discourage the so called “jurisprudência defensive”. It is necessary that the Courts reinforce its own role of creating and interpreting law, achieving decisions consistency, stability, predictability and legal certainty